Evolutionary history of two evergreen Rhododendron species as revealed by chromosome-level genome assembly - Wu, Xiaopei; Zhang, Lu; Wang, Xiuyun; Zhang, Rengang; Jin, Guihua; Hu, Yanting; Yang, Hong; Wu, Zhenzhen; Ma, Yongpeng; Zhang, Chengjun; Wang, Jihua (Frontiers in Plant Science, 2023)
The genus Rhododendron (Ericaceae), a species-rich and widely distributed genus of woody plants, is distinguished for the beautiful and diverse flowers and the correspondingly high ornamental and economic value. Here, we generate chromosome-scale genome assemblies for two evergreen Rhododendron species (Rhododendron delavayi Franch. and Rhododendron irroratum Franch., both 2n = 26), which are widely distributed in south-west China. Whole-genome duplication (WGD) analysis unveiled only one WGD event that occurred in Rhododendron after the ancestral γ triplication. Gene duplication and gene family expansion analyses suggested that the younger tandem and proximal duplications contributed greatly to the expansion of gene families involved in secondary metabolite biosynthesis and stress response. We identified several candidate R2R3-MYB genes likely regulating anthocyanin biosynthesis and stress tolerance in Rhododendron, which will facilitate the breeding for ornamental use. NBS-encoding genes, the largest disease resistance (R) gene family, had undergone significant expansion in Rhododendron species, which may have increased the resistance of these species to pathogenic organisms. This type of genes experienced species-specific gain and loss events in four Rhododendron plants, resulting in the current gene numbers, which were discrepant between species. Proximal duplication events appeared to be critical in the NBS-encoding gene family expansion. We believe that the reference genomes presented here will provide important genetic resources for molecular breeding and genetic improvement of plants in this economically important Rhododendron genus.